Integration of wireless sensor networks to the internet of things using a 6LoWPAN Gateway - Schrickte, L. F.; Montez, C.; Oliveira, R. de; Pinto, Alex R. [UNESP] (Ieee, 2014)
The Internet of Things is a new paradigm where smart embedded devices and systems are connected to the Internet. In this context, Wireless Sensor Networks (WSN) are becoming an important alternative for sensing and actuating critical applications like industrial automation, remote patient monitoring and domotics. The IEEE 802.15.4 protocol has been adopted as a standard for WSN and the 6LoWPAN protocol has been proposed to overcome the challenges of integrating WSN and Internet protocols. In this paper, the mechanisms of header compression and fragmentation of IPv6 datagrams proposed in the 6LoWPAN standard were evaluated through field experiments using a gateway prototype and IEEE 802.15.4 nodes.